Faktor Pendukung dan Faktor Penghambat Partisipasi Masyarakat Dalam Pelestarian Budaya Lokal Melalui Festival Bimbang Nagari Di Nagari Tluk Kualo Inderapura Kabupaten Pesisir Selatan - Muhammad Abdul Husen; Nora Eka putri (Jurnal Teori dan Riset Administrasi Publik, 2024)
AbstractThis research aims to find out what are the supporting and inhibiting factors for community participation in preserving local culture through the Bimbang Nagari festival in Nagari Tluk Kualo Inderapura. This research uses a quasi-qualitative research method with a simple research design. With data collection techniques through interviews, observation and documentation. The findings of this research indicate that the supporting factors and inhibiting factors for community participation in preserving local culture through the Bimbang Nagari Festival in Nagari Tluk Kualo Inderapura are: 1) The supporting factors for community participation in the Bimbang Nagari Festival are supported by the culture of mutual cooperation in the implementation of the Bimbang Nagari Festival by the community. Nagari Tluk Kualo Inderapura and the benefits of the Bimbang Nagari festival program for the people of Nagari Tluk Kualo Inderapura. 2) the factors inhibiting community participation in the Bimbang Nagari festival are influenced by the type of community work, where the majority of the community from Nagari Tluk Kualo Inderapura work as daily laborers and farmers. The lack of public knowledge about the importance of the Bimbang Nagari festival activities is also a factor inhibiting community participation in the Bimbang Nagari festival.